Can the Phenomenology of a Suicidal Crisis Be Usefully Understood As a Suite of Antipredator Defensive Reactions?. Issue 2 (2nd April 2016) - Joiner, Thomas E.; Stanley, Ian H.
Abstract : When perceiving a dangerous predation threat, mammalian and other species activate antipredator defensive reactions. These include the seemingly paradoxical—but compatible—activation of overarousal (e.g., agitation, insomnia) and "shutdown" (e.g., mutism, withdrawal) states. Acute suicidal crises, too, are characterized by the co-occurrence of overarousal and shutdown behaviors. In the minutes, hours, and days prior to one's death by suicide, it is not uncommon for one to be simultaneously agitated and socially withdrawn, states that resemble antipredator defensive reactions. In this article, we present empirical, clinical, and philosophical grist for our conjecture that antipredator defensive reactions may serve as a useful way to understand the phenomenology of a serious suicidal crisis, and we reflect on the implications that soon-to-be suicide decedents are simultaneously killer and victim.